Exterior material for all-solid-state battery and all-solid-state battery using the same

JP7631665B2Active Publication Date: 2025-02-19TOPPAN HOLDINGS INC
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2020029521
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-02-25
Publication Date
2025-02-19
Estimated Expiration
2040-02-25

AI Technical Summary

Benefits of technology

【0021】 本開示によれば、全固体電池の異常を早期に発見できる全固体電池用外装材及びそれを用いた全固体電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631665000002
    Figure 0007631665000002
  • Figure 0007631665000003
    Figure 0007631665000003
  • Figure 0007631665000004
    Figure 0007631665000004
Patent Text Reader

Abstract

To provide an exterior material for an all-solid battery, which allows an abnormality in an all-solid battery to be found at an early stage.SOLUTION: An exterior material for an all-solid battery has at least a base material layer, a barrier layer and a sealant layer in this order, and contains a sulfide-based solid electrolyte. Of the layers which constitute the exterior material, at least one layer contains a developer which reacts with hydrogen sulfide to change in color.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an exterior material for an all-solid-state battery and an all-solid-state battery using the same, and more particularly to an exterior material for an all-solid-state battery including a sulfide-based solid electrolyte and an all-solid-state battery using the same. [Background technology]

[0002] Secondary batteries such as lithium ion batteries are widely used in portable electronic devices, electric vehicles and hybrid electric vehicles that use electricity as a power source. As a battery with improved safety compared to lithium ion batteries, all-solid-state lithium batteries that use inorganic solid electrolytes instead of organic solvent electrolytes have been studied. All-solid-state lithium batteries are safer than lithium ion batteries in that they are less susceptible to thermal runaway caused by short circuits, etc.

[0003] Among inorganic solid electrolytes, sulfide-based solid electrolytes have a higher ionic conductivity than oxide-based solid electrolytes and have many advantages in obtaining a higher performance all-solid-state battery. However, since all-solid-state batteries using sulfide-based solid electrolytes contain sulfur, the moisture that has entered the battery may react with the sulfur to generate toxic hydrogen sulfide (H2S). Therefore, there is a concern that this hydrogen sulfide may leak out if the exterior material of the battery is destroyed. In order to prevent hydrogen sulfide from leaking out, for example, Patent Documents 1 and 2 propose all-solid-state batteries with a safety design that captures and detoxifies the generated hydrogen sulfide. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-103283 A [Patent Document 2] JP 2008-103288 A Summary of the Invention [Problem to be solved by the invention]

[0005] In an all-solid-state battery using a sulfide-based solid electrolyte, the generation of hydrogen sulfide means that some abnormality has occurred, such as the deterioration of the sulfide-based solid electrolyte or the damage of the exterior material. It is desirable to take measures such as replacing an all-solid-state battery in which such an abnormality has occurred promptly. However, since hydrogen sulfide has a pungent odor but is colorless, it is difficult to grasp that hydrogen sulfide is being generated. In addition, even if the methods described in Patent Documents 1 and 2 can detoxify the generated hydrogen sulfide, the abnormality of the all-solid-state battery itself cannot be eliminated, and there is a risk that the discovery of the abnormality will be delayed.

[0006] The present disclosure has been made in consideration of the problems associated with the above-described conventional techniques, and aims to provide an exterior material for an all-solid-state battery that enables early detection of an abnormality in the all-solid-state battery, and an all-solid-state battery using the same. [Means for solving the problem]

[0007] In order to achieve the above object, the present disclosure provides an exterior material for an all-solid-state battery containing a sulfide-based solid electrolyte, the exterior material having at least a substrate layer, a barrier layer, and a sealant layer in this order, wherein at least one of the layers constituting the exterior material contains a color developer that changes color upon reaction with hydrogen sulfide.

[0008] According to the above-mentioned exterior material, by providing a layer containing the above-mentioned color developer, when hydrogen sulfide is generated in an all-solid-state battery including a sulfide-based solid electrolyte, the layer containing the color developer changes color, so that the generation of hydrogen sulfide can be visually detected and abnormalities in the all-solid-state battery can be found early by visual inspection.

[0009] Here, when the substrate layer side of the exterior material is the outside and the sealant layer side is the inside, if a layer containing a color developer is provided inside the barrier layer, hydrogen sulfide generated inside the exterior material can be detected, and abnormalities in the all-solid-state battery can be visually detected at an early stage. If the barrier layer is opaque, discoloration of the layer inside the barrier layer can be confirmed, for example, by observing the end of the battery (cross section of the exterior material). The end of the battery can be observed visually or with a magnifying glass or microscope. On the other hand, if a layer containing a color developer is provided outside the barrier layer, if there is a defect such as a pinhole in the barrier layer, hydrogen sulfide generated inside the exterior material will penetrate through the defective part, and discoloration of the layer containing a color developer will become noticeable near the defective part, making it possible to detect abnormalities in the all-solid-state battery and also to easily identify the defective part. In addition, all-solid-state batteries are sometimes used in a modularized form. In the case where a layer containing a color developer is provided outside the barrier layer, if an abnormality occurs in any of the all-solid-state batteries in the module and hydrogen sulfide leaks out, discoloration will occur in the exterior materials of the surrounding all-solid-state batteries, making it easy to discover the abnormality in the module and to identify the all-solid-state battery in which the abnormality occurs.

[0010] The all-solid-state battery packaging material further includes at least one of a first adhesive layer disposed between the base layer and the barrier layer, a second adhesive layer disposed between the barrier layer and the sealant layer, and an adhesive resin layer disposed between the barrier layer and the sealant layer, and at least one layer selected from the group consisting of the first adhesive layer, the second adhesive layer, the adhesive resin layer, and the sealant layer may contain the color developer. When the specific layer contains a color developer, discoloration of the layer containing the color developer is likely to occur when hydrogen sulfide is generated in an all-solid-state battery containing a sulfide-based solid electrolyte, and early detection of abnormalities in the all-solid-state battery by visual inspection becomes easier.

[0011] The all-solid-state battery packaging material further comprises at least one of a first adhesive layer disposed between the base layer and the barrier layer, a second adhesive layer disposed between the barrier layer and the sealant layer, and an adhesive resin layer disposed between the barrier layer and the sealant layer, and a protective layer disposed on the surface of the base layer opposite to the barrier layer, and at least one layer selected from the group consisting of the protective layer, the first adhesive layer, the second adhesive layer, the adhesive resin layer, and the sealant layer may contain the color developer. When the specific layer contains a color developer, discoloration of the layer containing the color developer is likely to occur when hydrogen sulfide is generated in an all-solid-state battery containing a sulfide-based solid electrolyte, making it easier to visually detect an abnormality in the all-solid-state battery at an early stage.

[0012] In the all-solid-state battery exterior material, the color developer may contain at least one element selected from the group consisting of Cu, Pb, Ag, Mn, Ni, Co, Sn, and Cd. The color developer containing the above element is likely to react with sulfur in hydrogen sulfide and change color, and the color change is easily visible, making it easier to visually detect abnormalities in the all-solid-state battery at an early stage.

[0013] In the all-solid-state battery exterior material, the color developer may contain at least one selected from the group consisting of CuSO4, Pb(CH3COO)2, and Ag2SO4. The color developer containing the compound easily reacts with sulfur in hydrogen sulfide to change color, and the color change is easily visible, making it easier to visually detect abnormalities in the all-solid-state battery at an early stage.

[0014] In the all-solid-state battery exterior material, the content of the developer in the layer containing the developer may be 0.01% by mass or more and 30% by mass or less based on the total amount of the layer. When the content of the developer is equal to or more than the lower limit, the color change is more easily visible, and when the content is equal to or less than the upper limit, the deterioration of the function (e.g., adhesion strength, seal strength, etc.) of the layer containing the developer can be suppressed.

[0015] In the all-solid-state battery exterior material, at least one of the layers constituting the exterior material may contain a hydrogen sulfide adsorbing material that does not correspond to the color developer. In this case, in addition to early detection of abnormalities in the all-solid-state battery, generated hydrogen sulfide can be rendered harmless.

[0016] In the case where the substrate layer side of the all-solid-state battery packaging material is the outer side and the sealant layer side is the inner side, at least one of the layers arranged on the inner side of the barrier layer may contain the color developer, and at least one of the layers containing the color developer and the layer arranged on the barrier layer side of the layer containing the color developer may contain the hydrogen sulfide adsorption material. If the layer on the inner side of the layer containing the color developer contains the hydrogen sulfide adsorption material, hydrogen sulfide generated inside the packaging material may first come into contact with the hydrogen sulfide adsorption material and be adsorbed or decomposed, and the amount of hydrogen sulfide that reaches the layer containing the color developer may decrease, resulting in a small color change. In contrast, by including the hydrogen sulfide adsorption material in the specific layer, hydrogen sulfide generated inside the packaging material comes into contact with the layer containing the color developer to cause a color change in the layer, and then is adsorbed or decomposed by the hydrogen sulfide adsorption material contained in the same layer or a layer on the barrier layer side of the layer to be rendered harmless. Therefore, it is possible to achieve a high level of both color change due to hydrogen sulfide and rendering hydrogen sulfide harmless.

[0017] In the all-solid-state battery exterior material, the hydrogen sulfide adsorbent may contain zinc oxide and / or zinc ions. A hydrogen sulfide adsorbent containing zinc oxide and / or zinc ions is preferable because it has excellent performance in adsorbing or decomposing hydrogen sulfide and is inexpensive and easy to handle.

[0018] In the all-solid-state battery exterior material, the total content of the developer and the hydrogen sulfide adsorption substance in the layer containing the developer may be 0.01% by mass or more and 30% by mass or less based on the total amount of the layer.

[0019] In the all-solid-state battery packaging material, a corrosion prevention treatment layer may be provided on one or both surfaces of the barrier layer. By providing the corrosion prevention treatment layer, corrosion of the barrier layer can be prevented, and the presence of the corrosion prevention treatment layer can increase the adhesion between the barrier layer and the layer adjacent thereto. In addition, when a metal foil such as an aluminum foil is used as the barrier layer, the metal foil may be discolored by hydrogen sulfide, which may result in a decrease in barrier properties. In addition, water, acid, etc. may be generated as a reaction product between the color developer or the hydrogen sulfide adsorbent and hydrogen sulfide, and this product may cause corrosion of the metal foil. Such deterioration of the metal foil can be prevented by providing the corrosion prevention treatment layer.

[0020] The present disclosure also provides an all-solid-state battery including a battery element containing a sulfide-based solid electrolyte, a current extracting terminal extending from the battery element, and an exterior material for an all-solid-state battery according to the present disclosure that holds the current extracting terminal and houses the battery element. Effect of the Invention

[0021] According to the present disclosure, it is possible to provide an exterior packaging material for an all-solid-state battery that enables early detection of an abnormality in the all-solid-state battery, and an all-solid-state battery using the same. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a schematic cross-sectional view of an exterior material for an all-solid-state battery according to an embodiment of the present disclosure. [Diagram 2] FIG. 1 is a schematic cross-sectional view of an exterior material for an all-solid-state battery according to an embodiment of the present disclosure. [Diagram 3] FIG. 1 is a schematic cross-sectional view of an exterior material for an all-solid-state battery according to an embodiment of the present disclosure. [Figure 4] FIG. 1 is a perspective view of an all-solid-state battery according to an embodiment of the present disclosure. [Diagram 5] FIG. 2 is a schematic diagram illustrating a method for preparing a sample for measuring heat seal strength in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted. In addition, the dimensional ratios of the drawings are not limited to the ratios shown in the drawings.

[0024] [Exterior material for all-solid-state batteries] Fig. 1 is a cross-sectional view showing a schematic diagram of an embodiment of the all-solid-state battery exterior material of the present disclosure. As shown in Fig. 1, the exterior material (all-solid-state battery exterior material) 10 of this embodiment is a laminated body including a substrate layer 11, a first adhesive layer 12a provided on one side of the substrate layer 11, a barrier layer 13 having first and second corrosion prevention treatment layers 14a, 14b on both sides provided on the side of the first adhesive layer 12a opposite the substrate layer 11, a second adhesive layer 12b provided on the side of the barrier layer 13 opposite the first adhesive layer 12a, and a sealant layer 16 provided on the side of the second adhesive layer 12b opposite the barrier layer 13. Here, the first corrosion prevention treatment layer 14a is provided on the surface of the barrier layer 13 facing the substrate layer 11, and the second corrosion prevention treatment layer 14b is provided on the surface of the barrier layer 13 facing the sealant layer 16. In the exterior material 10, the base material layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, the exterior material 10 is used with the base material layer 11 facing the exterior side of the all-solid-state battery, and the sealant layer 16 facing the interior side of the all-solid-state battery.

[0025] At least one of the layers constituting the packaging material 10 of this embodiment contains a color developer that changes color upon reaction with hydrogen sulfide. At least one of the layers constituting the packaging material 10 of this embodiment may contain a hydrogen sulfide adsorbing material. Each layer constituting the packaging material 10 will be specifically described below.

[0026] <Base material layer 11> The base layer 11 provides heat resistance in a sealing process when manufacturing an all-solid-state battery and plays a role in suppressing the occurrence of pinholes that may occur during molding and distribution. In particular, in the case of an exterior material for an all-solid-state battery for large-scale use, the base layer 11 can also provide scratch resistance, chemical resistance, insulation, and the like.

[0027] The base layer 11 is preferably a layer formed of an insulating resin, such as polyester resin, polyamide resin, polyimide resin, polyamideimide resin, polyetherketone resin, polyphenylene sulfide resin, polyetherimide resin, polysulfone resin, fluororesin, phenol resin, melamine resin, urethane resin, allyl resin, silicone resin, epoxy resin, furan resin, acetyl cellulose resin, or the like.

[0028] When these resins are applied to the base layer 11, they may be in the form of a stretched or unstretched film, or in the form of a coating film. The base layer 11 may be a single layer or a multilayer, and in the case of a multilayer, different resins may be used in combination. In the case of a film, a co-extruded film or a film laminated with an adhesive may be used. In the case of a coating film, a film coated the number of times that it is laminated may be used, and a film and a coating film may be combined to form a multilayer.

[0029] Among these resins, polyester resin and polyamide resin are preferable for the base layer 11 because of their excellent moldability. Examples of polyester resin include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of polyamide resin constituting the polyamide film include nylon 6, nylon 6,6, a copolymer of nylon 6 and nylon 6,6, nylon 6, nylon 9T, nylon 10, polymetaxylylene adipamide (MXD6), nylon 11, and nylon 12.

[0030] When these resins are used in the form of a film, it is preferably a biaxially stretched film. Examples of the stretching method for the biaxially stretched film include sequential biaxial stretching, tubular biaxial stretching, and simultaneous biaxial stretching. From the viewpoint of obtaining better deep drawing formability, the biaxially stretched film is preferably one stretched by the tubular biaxial stretching method.

[0031] The thickness of the substrate layer 11 is preferably 6 to 40 μm, and more preferably 10 to 30 μm. When the thickness of the substrate layer 11 is 6 μm or more, the pinhole resistance and insulating properties of the packaging material 10 tend to be improved. When the thickness of the substrate layer 11 exceeds 40 μm, the total thickness of the packaging material 10 tends to be large.

[0032] In order to suppress deformation of the base layer 11 during sealing, the peak melting temperature of the base layer 11 is higher than the peak melting temperature of the sealant layer 16, and is preferably 30° C. or more higher than the peak melting temperature of the sealant layer 16.

[0033] <First adhesive layer 12a> The first adhesive layer 12a is a layer that bonds the base layer 11 and the barrier layer 13. Specific examples of materials constituting the first adhesive layer 12a include polyurethane resins in which a bifunctional or higher isocyanate compound (polyfunctional isocyanate compound) is reacted with a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol. The above-mentioned various polyols can be used alone or in combination of two or more types depending on the function and performance required for the exterior material 10. In addition to the above, a base material containing an epoxy resin and a curing agent can also be used, but is not limited to this. In addition, the above-mentioned adhesives may be mixed with various other additives and stabilizers depending on the performance required for the adhesive.

[0034] The thickness of the first adhesive layer 12a is not particularly limited, but from the viewpoint of obtaining the desired adhesive strength, followability, processability, and the like, the thickness is, for example, preferably 1 to 10 μm, and more preferably 2 to 7 μm.

[0035] <Barrier layer 13> The barrier layer 13 has a water vapor barrier property that prevents moisture from penetrating into the inside of the all-solid-state battery. The barrier layer 13 may also have extensibility for deep drawing. As the barrier layer 13, for example, various metal foils such as aluminum, stainless steel, copper, etc., or metal vapor deposition films, inorganic oxide vapor deposition films, carbon-containing inorganic oxide vapor deposition films, films provided with these vapor deposition films, etc. can be used. As the film provided with the vapor deposition film, for example, an aluminum vapor deposition film or an inorganic oxide vapor deposition film can be used. These can be used alone or in combination of two or more. As the barrier layer 13, a metal foil is preferable, and an aluminum foil is more preferable, in terms of mass (specific gravity), moisture resistance, processability, and cost.

[0036] As the aluminum foil, a soft aluminum foil that has been annealed can be preferably used from the viewpoint of imparting desired ductility during molding, but it is more preferable to use an aluminum foil containing iron for the purpose of imparting further pinhole resistance and ductility during molding. The content of iron in the aluminum foil is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%, in 100 mass% of the aluminum foil. When the iron content is 0.1 mass% or more, an exterior material 10 having better pinhole resistance and ductility can be obtained. When the iron content is 9.0 mass% or less, an exterior material 10 having better flexibility can be obtained. As the aluminum foil, an untreated aluminum foil may be used, but it is preferable to use an aluminum foil that has been degreased in terms of imparting corrosion resistance. When the aluminum foil is degreased, the degreased treatment may be performed on only one side of the aluminum foil, or on both sides.

[0037] The thickness of the barrier layer 13 is not particularly limited, but taking into consideration the barrier properties, pinhole resistance, and processability, it is preferably 9 to 200 μm, and more preferably 15 to 100 μm.

[0038] <First and second corrosion prevention treatment layers 14a, 14b> The first and second corrosion prevention layers 14a and 14b are layers provided to prevent corrosion of the metal foil (metal foil layer) constituting the barrier layer 13. The first corrosion prevention layer 14a plays a role in increasing the adhesion between the barrier layer 13 and the first adhesive layer 12a. The second corrosion prevention layer 14b plays a role in increasing the adhesion between the barrier layer 13 and the second adhesive layer 12b. The first corrosion prevention layer 14a and the second corrosion prevention layer 14b may be layers of the same configuration or layers of different configurations. The first and second corrosion prevention layers 14a and 14b (hereinafter also simply referred to as "corrosion prevention layers 14a and 14b") are formed, for example, by degreasing treatment, hydrothermal conversion treatment, anodizing treatment, chemical conversion treatment, or a combination of these treatments.

[0039] Examples of the degreasing treatment include acid degreasing and alkaline degreasing. Examples of the acid degreasing include a method using an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or hydrofluoric acid alone or a mixture of these. In addition, by using an acid degreasing agent in which a fluorine-containing compound such as monosodium ammonium difluoride is dissolved in the inorganic acid as described above, not only can the aluminum be degreased, but also a passive aluminum fluoride can be formed, which is effective in terms of corrosion resistance, particularly when an aluminum foil is used for the barrier layer 13. Examples of the alkaline degreasing include a method using sodium hydroxide or the like.

[0040] An example of the hydrothermal modification treatment is boehmite treatment in which an aluminum foil is immersed in boiling water containing triethanolamine. An example of the anodization treatment is alumite treatment.

[0041] The chemical conversion treatment may be of the immersion type or the coating type. Examples of the immersion type chemical conversion treatment include chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, and various chemical conversion treatments consisting of a mixture of these. On the other hand, examples of the coating type chemical conversion treatment include a method in which a coating agent having corrosion prevention properties is applied onto the barrier layer 13.

[0042] When forming at least a part of the corrosion prevention layer by any of these corrosion prevention treatments, namely, hydrothermal conversion treatment, anodizing treatment, and chemical conversion treatment, it is preferable to perform the above-mentioned degreasing treatment in advance. Note that, when using a degreased metal foil, such as a metal foil that has been subjected to an annealing process, as the barrier layer 13, there is no need to perform a degreasing treatment again in forming the corrosion prevention layers 14a and 14b.

[0043] The coating agent used in the spray-type chemical conversion treatment preferably contains trivalent chromium. The coating agent may also contain at least one polymer selected from the group consisting of cationic polymers and anionic polymers, which will be described later.

[0044] Among the above treatments, particularly in hydrothermal conversion treatment and anodization treatment, the aluminum foil surface is dissolved by a treatment agent to form an aluminum compound (boehmite, alumite) having excellent corrosion resistance. Therefore, since a bicontinuous structure is formed from the barrier layer 13 using the aluminum foil to the corrosion prevention treatment layers 14a, 14b, the above treatment is included in the definition of chemical conversion treatment. On the other hand, as described later, it is also possible to form the corrosion prevention treatment layers 14a, 14b by a pure coating method that is not included in the definition of chemical conversion treatment. As an example of this method, a method using a sol of a rare earth element oxide such as cerium oxide with an average particle size of 100 nm or less can be mentioned, which has an aluminum corrosion prevention effect (inhibitor effect) and is also environmentally friendly. By using this method, it is possible to impart a corrosion prevention effect to metal foils such as aluminum foils even with a general coating method.

[0045] Examples of the rare earth element oxide sol include sols using various solvents such as water-based, alcohol-based, hydrocarbon-based, ketone-based, ester-based, ether-based, etc. Among these, water-based sols are preferred.

[0046] In order to stabilize the dispersion of the rare earth oxide sol, inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid, etc. or their salts, and organic acids such as acetic acid, malic acid, ascorbic acid, lactic acid, etc. are usually used as dispersion stabilizers. Among these dispersion stabilizers, phosphoric acid in particular is expected to provide the following in the exterior packaging material 10: (1) sol dispersion stabilization, (2) improvement of adhesion to the barrier layer 13 by utilizing phosphoric acid's aluminum chelating ability, (3) imparting corrosion resistance by capturing aluminum ions (passivation formation), and (4) improvement of the cohesive force of the corrosion prevention treatment layers (oxide layers) 14a, 14b by easily causing dehydration condensation of phosphoric acid even at low temperatures.

[0047] The corrosion prevention layers 14a and 14b formed from the rare earth oxide sol are aggregates of inorganic particles, and therefore may lose their cohesive strength even after the drying and curing process. Therefore, it is preferable that the corrosion prevention layers 14a and 14b in this case are compounded with an anionic polymer or a cationic polymer to compensate for the cohesive strength.

[0048] The corrosion prevention treatment layers 14a, 14b are not limited to the above-mentioned layers. For example, they may be formed using a treatment agent in which phosphoric acid and a chromium compound are mixed with a resin binder (such as aminophenol), as in the case of coating-type chromate, which is a known technology. By using this treatment agent, a layer having both corrosion prevention function and adhesion can be formed. In addition, although it is necessary to consider the stability of the coating liquid, a coating agent in which a rare earth oxide sol and a polycationic polymer or a polyanionic polymer are mixed in advance into a one-component solution can be used to form a layer having both corrosion prevention function and adhesion.

[0049] The mass per unit area of ​​the corrosion prevention layers 14a and 14b is 0.005 to 0.200 g / m2 regardless of whether the layer has a multi-layer structure or a single-layer structure. 2 is preferable, and 0.010 to 0.100 g / m 2 It is more preferable that the mass per unit area is 0.005 g / m 2 If the mass per unit area is 0.200 g / m or more, it is easy to impart a corrosion prevention function to the barrier layer 13. 2 Even if the thickness exceeds 100 mm, the corrosion prevention function does not change much. On the other hand, when a rare earth oxide sol is used, if the coating is thick, the heat curing during drying may be insufficient, which may result in a decrease in cohesive force. The thickness of the corrosion prevention layers 14a and 14b can be calculated from their specific gravity.

[0050] From the viewpoint of easily maintaining the adhesion between the sealant layer and the barrier layer, the corrosion prevention treatment layers 14a, 14b may be in an embodiment containing, for example, cerium oxide, 1 to 100 parts by mass of phosphoric acid or a phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer, or may be formed by subjecting the barrier layer 13 to a chemical conversion treatment, or may be formed by subjecting the barrier layer 13 to a chemical conversion treatment and contain a cationic polymer.

[0051] <Second adhesive layer 12b> The second adhesive layer 12b is a layer that bonds the barrier layer 13 and the sealant layer 16. For the second adhesive layer 12b, a general adhesive for bonding the barrier layer 13 and the sealant layer 16 can be used.

[0052] When a corrosion prevention treatment layer 14b is provided on the barrier layer 13, and the second corrosion prevention treatment layer 14b has a layer containing at least one polymer selected from the group consisting of the above-mentioned cationic polymers and anionic polymers, the second adhesive layer 12b is preferably a layer containing a compound (hereinafter also referred to as a "reactive compound") that is reactive with the above-mentioned polymer contained in the second corrosion prevention treatment layer 14b.

[0053] For example, when the second corrosion prevention treatment layer 14b contains a cationic polymer, the second adhesive layer 12b contains a compound reactive with the cationic polymer. When the second corrosion prevention treatment layer 14b contains an anionic polymer, the second adhesive layer 12b contains a compound reactive with the anionic polymer. When the second corrosion prevention treatment layer 14b contains a cationic polymer and an anionic polymer, the second adhesive layer 12b contains a compound reactive with the cationic polymer and a compound reactive with the anionic polymer. However, the second adhesive layer 12b does not necessarily have to contain the above two types of compounds, and may contain a compound reactive with both the cationic polymer and the anionic polymer. Here, "reactive" means to form a covalent bond with the cationic polymer or the anionic polymer. The second adhesive layer 12b may further contain an acid-modified polyolefin resin.

[0054] The compound reactive with the cationic polymer may be at least one compound selected from the group consisting of a polyfunctional isocyanate compound, a glycidyl compound, a compound having a carboxy group, and a compound having an oxazoline group.

[0055] Examples of the polyfunctional isocyanate compound, glycidyl compound, compound having a carboxy group, and compound having an oxazoline group include the polyfunctional isocyanate compound, glycidyl compound, compound having a carboxy group, and compound having an oxazoline group, which are exemplified above as crosslinking agents for forming a crosslinked structure from a cationic polymer. Among these, the polyfunctional isocyanate compound is preferred in terms of high reactivity with the cationic polymer and ease of forming a crosslinked structure.

[0056] The compound reactive with anionic polymers includes at least one compound selected from the group consisting of glycidyl compounds and compounds having oxazoline groups.These glycidyl compounds and compounds having oxazoline groups include the glycidyl compounds and compounds having oxazoline groups exemplified above as crosslinking agents for forming cationic polymers into crosslinked structures.Among these, glycidyl compounds are preferred because of their high reactivity with anionic polymers.

[0057] When the second adhesive layer 12b contains an acid-modified polyolefin resin, it is preferable that the reactive compound is also reactive with the acidic group in the acid-modified polyolefin resin (i.e., forms a covalent bond with the acidic group). This further enhances the adhesion to the second corrosion prevention treatment layer 14b. In addition, the acid-modified polyolefin resin has a crosslinked structure, which further improves the solvent resistance of the exterior material 10.

[0058] The content of the reactive compound is preferably from an equivalent amount to 10 times the equivalent amount of the acidic group in the acid-modified polyolefin resin. If it is an equivalent amount or more, the reactive compound reacts sufficiently with the acidic group in the acid-modified polyolefin resin. On the other hand, if it exceeds 10 times the equivalent amount, the crosslinking reaction with the acid-modified polyolefin resin is sufficiently saturated, so that there is a concern of the presence of unreacted substances and a decrease in various performances. Therefore, for example, the content of the reactive compound is preferably 5 to 20 parts by mass (solid content ratio) per 100 parts by mass of the acid-modified polyolefin resin.

[0059] The acid-modified polyolefin resin is a polyolefin resin to which an acidic group has been introduced. Examples of the acidic group include a carboxyl group, a sulfonic acid group, and an acid anhydride group, and maleic anhydride groups and (meth)acrylic acid groups are particularly preferred. For example, the acid-modified polyolefin resin may be the same as the modified polyolefin resin used in the sealant layer 16.

[0060] The second adhesive layer 12b may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, and a tackifier.

[0061] The second adhesive layer 12b may contain, for example, an acid-modified polyolefin and at least one curing agent selected from the group consisting of a polyfunctional isocyanate compound, a glycidyl compound, a compound having a carboxy group, a compound having an oxazoline group, and a carbodiimide compound, from the viewpoint of suppressing a decrease in laminate strength when corrosive gases such as hydrogen sulfide or an electrolyte are involved and from the viewpoint of further suppressing a decrease in insulating properties. Examples of the carbodiimide compound include N,N'-di-o-toluylcarbodiimide, N,N'-diphenylcarbodiimide, N,N'-di-2,6-dimethylphenylcarbodiimide, N,N'-bis(2,6-diisopropylphenyl)carbodiimide, N,N'-dioctyldecylcarbodiimide, N-triyl-N'-cyclohexylcarbodiimide, N,N'-di-2,2-di-t-butylphenylcarbodiimide, N-triyl-N'-phenylcarbodiimide, N,N'-di-p-nitrophenylcarbodiimide, N,N'-di-p-aminophenylcarbodiimide, N,N'-di-p-hydroxyphenylcarbodiimide, N,N'-di-cyclohexylcarbodiimide, and N,N'-di-p-toluylcarbodiimide.

[0062] In addition, as the adhesive for forming the second adhesive layer 12b, for example, a polyurethane adhesive obtained by blending polyester polyol made of hydrogenated dimer fatty acid and diol with polyisocyanate can be used. Examples of adhesives include polyurethane resins obtained by reacting a bifunctional or higher isocyanate compound with a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol, and epoxy resins obtained by reacting an amine compound with a base material having an epoxy group, which are preferable from the viewpoint of heat resistance.

[0063] The thickness of the second adhesive layer 12b is not particularly limited, but from the viewpoint of obtaining the desired adhesive strength, processability, and the like, it is preferably 1 to 10 μm, and more preferably 2 to 7 μm.

[0064] <Sealant layer 16> The sealant layer 16 is a layer that imparts heat-sealing sealability to the exterior material 10, and is a layer that is disposed on the inside and heat-sealed (thermally fused) when assembling the all-solid-state battery.

[0065] Examples of the sealant layer 16 include resin films made of polyolefin resins or polyester resins. These resins (hereinafter also referred to as "base resins") constituting the sealant layer 16 may be used alone or in combination of two or more kinds.

[0066] Examples of polyolefin resins include low-, medium- or high-density polyethylene; ethylene-α-olefin copolymers; polypropylene; block or random copolymers containing propylene as a copolymerization component; and propylene-α-olefin copolymers.

[0067] Examples of polyester resins include polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate (PBN) resin, and copolymers thereof.

[0068] The sealant layer 16 may contain a polyolefin-based elastomer. The polyolefin-based elastomer may be compatible with the above-mentioned base resin or may not be compatible with it, and may contain both a compatible polyolefin-based elastomer that is compatible and a non-compatible polyolefin-based elastomer that is not compatible with it. Being compatible (compatible system) means that the elastomer disperses in the base resin with a dispersed phase size of 1 nm or more and less than 500 nm. Not being compatible (non-compatible system) means that the elastomer disperses in the base resin with a dispersed phase size of 500 nm or more and less than 20 μm.

[0069] When the base resin is a polypropylene resin, the compatible polyolefin elastomer may be, for example, a propylene-butene-1 random copolymer, and the incompatible polyolefin elastomer may be, for example, an ethylene-butene-1 random copolymer. The polyolefin elastomers may be used alone or in combination of two or more.

[0070] Furthermore, the sealant layer 16 may contain, as additive components, for example, slip agents, antiblocking agents, antioxidants, light stabilizers, flame retardants, etc. The content of these additive components is preferably 5 parts by mass or less, assuming that the total mass of the sealant layer 16 is 100 parts by mass.

[0071] The thickness of the sealant layer 16 is not particularly limited, but from the viewpoint of achieving both a thin film and improved heat seal strength in a high-temperature environment, it is preferably in the range of 5 to 100 μm, more preferably in the range of 10 to 100 μm, and even more preferably in the range of 20 to 80 μm.

[0072] The sealant layer 16 may be either a single-layer film or a multi-layer film, and may be selected depending on the required function.

[0073] <Developer> At least one of the layers constituting the exterior material 10 of this embodiment contains a color developer that changes color upon reaction with hydrogen sulfide. In the exterior material 10, the color developer may be contained in at least one layer selected from the group consisting of the first adhesive layer 12a, the second adhesive layer 12b, and the sealant layer 16. When the color developer is contained in any layer inside the barrier layer 13 (the sealant layer 16 side), the color developer is preferably contained in the sealant layer 16. Since the sealant layer 16 is the innermost layer in the exterior material 10, by containing the color developer in the sealant layer 16, hydrogen sulfide generated inside the exterior material 10 is likely to come into contact with the color developer, and the color developer reacts with hydrogen sulfide to cause the sealant layer 16 to discolor quickly. In addition, since the sealant layer 16 is usually thicker than the second adhesive layer 12b, it is easier to confirm discoloration when observing the cross section of the exterior material 10 when the sealant layer 16 contains the color developer. The color developer may be contained in only one of the layers constituting the packaging material 10, or may be contained in two or more layers.

[0074] The color developer may contain at least one element selected from the group consisting of Cu, Pb, Ag, Mn, Ni, Co, Sn, and Cd. The above elements react quickly with hydrogen sulfide in an ionized state and discolor. Cu and Ag also react with hydrogen sulfide in the atmosphere and discolor even in their metallic state. From the viewpoint of ease of discoloration, it is preferable that the above elements exist in an ionized state or in a state that is easily ionized.

[0075] The color developer may contain at least one selected from the group consisting of CuSO4, Pb(CH3COO)2, and Ag2SO4. These compounds tend to be easily hydrated, and the metal elements tend to be easily ionized. Therefore, the color developer containing the above compound reacts with the sulfur of hydrogen sulfide and changes color easily, and the color change is easily visible, making it easier to visually detect abnormalities in the all-solid-state battery at an early stage. The above compound may be present in a hydrated state.

[0076] A metal soap such as zinc stearate may be added to the layer to which the developer is added in order to improve the dispersibility of the developer. By using the developer in combination with the metal soap, the dispersibility of the developer in the layer can be improved, which makes it easier to suppress uneven discoloration and also makes it easier to suppress a decrease in the functionality (e.g., adhesion strength, seal strength, etc.) of the layer containing the developer.

[0077] When the developer is added to the sealant layer 16 or the adhesive resin layer 15 described later, the developer may be dispersed in advance in a resin such as polyethylene or polypropylene at a high concentration (e.g., 30% by mass or more) to prepare a master batch, which may then be mixed with other resins when performing extrusion lamination or the like. The above-mentioned metal soap may also be added when preparing this master batch. By preparing a master batch, the developer can be more easily dispersed in the layer, making it easier to suppress uneven discoloration and to suppress a decrease in the functionality (e.g., adhesion strength, seal strength, etc.) of the layer containing the developer.

[0078] The content of the developer in the layer containing the developer may be 0.01% by mass to 30% by mass, 0.05% by mass to 20% by mass, or 0.1% by mass to 15% by mass, based on the total amount of the layer. When the content of the developer is equal to or more than the lower limit, the color change is more easily visible, and when the content is equal to or less than the upper limit, the deterioration of the function (e.g., adhesion strength, seal strength, etc.) of the layer containing the developer can be suppressed.

[0079] The layer containing the developer may be cut into a size of 50 mm x 50 mm, sealed in a container (e.g., a 2-liter Tedlar bag) together with 2 L of H2S gas having a concentration of 5 ppm by mass, and left at room temperature (25°C) for 72 hours. The color difference (ΔE) before and after the test may be 0.5 or more. When the color difference (ΔE) is equal to or greater than the lower limit, it becomes easier to visually recognize discoloration of the layer containing the developer. In particular, when the developer is contained in any layer on the inner side (sealant layer 16 side) of the barrier layer 13, it becomes easier to visually recognize discoloration by observing the cross section of the exterior material 10. The color difference (ΔE) can be measured using a color difference meter. The color difference (ΔE) can be adjusted, for example, by the type and amount of the developer, and, when a hydrogen sulfide adsorbent is added to the same layer, the type and amount of the hydrogen sulfide adsorbent.

[0080] <Hydrogen sulfide adsorption material> At least one of the layers constituting the packaging material 10 of this embodiment may contain a hydrogen sulfide adsorption substance. In this specification, the hydrogen sulfide adsorption substance means a substance that does not correspond to the above-mentioned color developer (i.e., does not change color even when in contact with hydrogen sulfide) and can adsorb and / or decompose hydrogen sulfide. In the packaging material 10, the hydrogen sulfide adsorption substance may be contained in at least one layer selected from the group consisting of the first adhesive layer 12a, the second adhesive layer 12b, and the sealant layer 16. The hydrogen sulfide adsorption substance may be contained in a layer containing a color developer, or may be contained in a layer not containing a color developer. In addition, when a color developer is contained in any layer on the inner side of the barrier layer 13 (sealant layer 16 side), it is preferable that the hydrogen sulfide adsorption substance is contained in at least one layer of the layer containing the color developer and the layer arranged on the barrier layer 13 side. That is, when the color developer is contained inside the barrier layer 13 in the packaging material 10, it is preferable that the color developer is contained in the sealant layer 16, and the hydrogen sulfide adsorbing substance is contained in the sealant layer 16 and / or the second adhesive layer 12b. When the color developer is contained inside the barrier layer 13, the hydrogen sulfide adsorbing substance may be contained in the first adhesive layer 12a. The hydrogen sulfide adsorbing substance may be contained in only one of the layers constituting the packaging material 10, or in two or more layers.

[0081] Examples of hydrogen sulfide adsorbing substances include zinc oxide, amorphous metal silicates (mainly those in which the metal is copper or zinc), hydrates of zirconium and tantanide elements, tetravalent metal phosphates (particularly those in which the metal is copper), mixtures of zeolite and zinc ions, mixtures of zeolite, zinc oxide, and copper (II) oxide, potassium permanganate, sodium permanganate, silver sulfate, silver acetate, aluminum oxide, iron hydroxide, isocyanate compounds, aluminum silicate, potassium aluminum sulfate, zeolite, activated carbon, amine compounds, and ionomers. In addition, the hydrogen sulfide adsorbing substance is preferably one that contains zinc oxide (ZnO) and / or zinc ions, which can more easily render hydrogen sulfide harmless, and is advantageous in terms of cost and ease of handling. The hydrogen sulfide adsorbing substances can be used alone or in combination of two or more.

[0082] As the hydrogen sulfide adsorbent, the following deodorants having a deodorizing effect on hydrogen sulfide may be used. Specific examples include "Daimshoo PE-M 3000-Z" (polyethylene masterbatch product) manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., "Kesmon" manufactured by Toagosei Co., Ltd., "Shoe Cleanse" manufactured by Rasa Kogyo Co., Ltd., and "Dashlight ZU" and "Dashlight CZU" manufactured by Sinanen Zeomic Co., Ltd.

[0083] When the hydrogen sulfide adsorbing substance is colored, the color is preferably one that does not hinder the visual recognition of the discoloration of the color developer, and is preferably one that makes the discoloration of the color developer easier to visually recognize. The color of the hydrogen sulfide adsorbing substance may be adjusted according to the color of the color developer used before and after discoloration. For example, when the hydrogen sulfide adsorbing substance is white, etc., this is preferable because the discoloration of the color developer tends to be easier to visually recognize. On the other hand, when the hydrogen sulfide adsorbing substance is brown or black, etc., the discoloration of the color developer tends to be harder to visually recognize.

[0084] A metal soap such as zinc stearate may be added to the layer to which the hydrogen sulfide adsorbent is added, from the viewpoint of improving the dispersibility of the hydrogen sulfide adsorbent. By using the hydrogen sulfide adsorbent in combination with the metal soap, the dispersibility of the hydrogen sulfide adsorbent in the layer can be increased, the effect of detoxifying hydrogen sulfide is less likely to be biased, and the deterioration of the function (e.g., adhesion strength, seal strength, etc.) of the layer containing the hydrogen sulfide adsorbent can be easily suppressed.

[0085] The hydrogen sulfide adsorbing substance may be used in the form of a master batch in the same manner as the color developer. When the hydrogen sulfide adsorbing substance and the color developer are added to the same layer, the hydrogen sulfide adsorbing substance and the color developer may be used in the form of a master batch.

[0086] The content of the hydrogen sulfide adsorbing substance in the layer containing the hydrogen sulfide adsorbing substance may be 0.01% by mass to 30% by mass, 0.05% by mass to 20% by mass, or 0.1% by mass to 15% by mass, based on the total amount of the layer. When the content of the hydrogen sulfide adsorbing substance is equal to or more than the lower limit, the effect of rendering hydrogen sulfide harmless is easily obtained, and when the content is equal to or less than the upper limit, deterioration of the function (e.g., adhesion strength, seal strength, etc.) of the layer containing the hydrogen sulfide adsorbing substance can be suppressed.

[0087] When both the developer and the hydrogen sulfide adsorption substance are contained in the same layer, the total content of the developer and the hydrogen sulfide adsorption substance in the layer may be 0.01% by mass to 30% by mass, 0.05% by mass to 20% by mass, or 0.1% by mass to 15% by mass, based on the total amount of the layer. When this content is equal to or more than the lower limit, the color change is more easily visible and the effect of detoxifying hydrogen sulfide is more easily obtained, and when it is equal to or less than the upper limit, the deterioration of the function (e.g., adhesion strength, seal strength, etc.) of the layer containing the developer and the hydrogen sulfide adsorption substance can be suppressed.

[0088] Although the preferred embodiment of the exterior material for an all-solid-state battery according to the present embodiment has been described in detail above, the present disclosure is not limited to such a specific embodiment, and various modifications and changes are possible within the scope of the gist of the present disclosure described in the claims.

[0089] For example, FIG. 1 shows a case where anti-corrosion treatment layers 14a, 14b are provided on both sides of the barrier layer 13, but only one of the anti-corrosion treatment layers 14a, 14b may be provided, or no anti-corrosion treatment layer may be provided.

[0090] Furthermore, when the color developer is contained in any layer on the inner side of the barrier layer 13 (the sealant layer 16 side), a part of the layer containing the color developer may be exposed in order to make it easier to check the discoloration of the layer containing the color developer. For example, a cutout may be provided in the exterior material 10 so that a part of the layer containing the color developer is exposed. Furthermore, the layer containing the color developer may be shaped so that a part of the layer protrudes more than the other layers. Furthermore, the layer containing the color developer may be stacked with a shift from the other layers so that a part of the layer containing the color developer is exposed.

[0091] 1 shows a case where the barrier layer 13 and the sealant layer 16 are laminated using the second adhesive layer 12b, but the barrier layer 13 and the sealant layer 16 may be laminated using an adhesive resin layer 15 as in the all-solid-state battery packaging material 20 shown in Fig. 2. In addition, in the all-solid-state battery packaging material 20 shown in Fig. 2, the second adhesive layer 12b may be provided between the barrier layer 13 and the adhesive resin layer 15.

[0092] <Adhesive resin layer 15> The adhesive resin layer 15 is generally composed of an adhesive resin composition as a main component and additive components as necessary. The adhesive resin composition is not particularly limited, but preferably contains a modified polyolefin resin.

[0093] The modified polyolefin resin is preferably a polyolefin resin graft-modified with an unsaturated carboxylic acid derivative derived from an unsaturated carboxylic acid, an acid anhydride, or an ester thereof.

[0094] Examples of polyolefin resins include low density polyethylene, medium density polyethylene, high density polyethylene, ethylene-α-olefin copolymer, homopolypropylene, block polypropylene, random polypropylene, and propylene-α-olefin copolymer.

[0095] The modified polyolefin resin is preferably a polyolefin resin modified with maleic anhydride. For example, "Admer" manufactured by Mitsui Chemicals, Inc. and "Modic" manufactured by Mitsubishi Chemical Corporation are suitable for the modified polyolefin resin. Since such modified polyolefin resins have excellent reactivity with various metals and polymers having various functional groups, the adhesive resin layer 15 can be given adhesion by utilizing the reactivity. In addition, the adhesive resin layer 15 may contain various additives such as various compatible and incompatible elastomers, flame retardants, slip agents, antiblocking agents, antioxidants, light stabilizers, and tackifiers, as necessary.

[0096] The thickness of the adhesive resin layer 15 is not particularly limited, but from the viewpoints of stress relaxation and moisture permeability, it is preferably the same as or less than that of the sealant layer 16 .

[0097] In addition, in the all-solid-state battery exterior material 20, the total thickness of the adhesive resin layer 15 and the sealant layer 16 is preferably in the range of 5 to 100 μm, and more preferably in the range of 20 to 80 μm, from the viewpoint of achieving both a thin film and improved heat seal strength in a high-temperature environment.

[0098] In the packaging material 20, the color developer and / or the hydrogen sulfide adsorption substance may be contained in the adhesive resin layer 15. In the packaging material 20, the color developer and / or the hydrogen sulfide adsorption substance may be contained in at least one layer selected from the group consisting of the first adhesive layer 12a, the adhesive resin layer 15, and the sealant layer 16.

[0099] The exterior material of the present disclosure may further include a protective layer 17 arranged on the surface of the base material layer 11 opposite to the barrier layer 13, as in the exterior material 30 for an all-solid-state battery shown in Fig. 3. In Fig. 3, the adhesive resin layer 15 may be a second adhesive layer 12b.

[0100] <Protective layer 17> The protective layer 17 is a layer that protects the base layer 11. The same material as that of the first adhesive layer 12a can be used as a material constituting the protective layer 17. The protective layer 17 can be formed on the base layer 11 by coating or the like.

[0101] In the exterior packaging material 30, the color developer and / or the hydrogen sulfide adsorption substance may be contained in the protective layer 17. In the exterior packaging material 30, the color developer and / or the hydrogen sulfide adsorption substance may be contained in at least one layer selected from the group consisting of the protective layer 17, the first adhesive layer 12a, the adhesive resin layer 15, and the sealant layer 16.

[0102] In the case where the color developer is contained in any layer on the outer side (substrate layer 11 side) of the barrier layer 13 in the exterior material 30, the color developer may be contained in the protective layer 17 or the first adhesive layer 12a depending on the purpose. When the color developer is contained in the protective layer 17, since the protective layer 17 is the outermost layer in the exterior material 10, in the case where an abnormality occurs in any all-solid-state battery in the module and hydrogen sulfide leaks, it becomes easy to find the abnormality in the module and to identify the all-solid-state battery in which the abnormality occurs. On the other hand, when the color developer is contained in the first adhesive layer 12a, when there is a defect such as a pinhole in the barrier layer 13, the discoloration of the first adhesive layer 12a becomes noticeable in the vicinity of the defective part, and it becomes easy to find the abnormality in the all-solid-state battery and to identify the defective part. The color developer may be contained in both the protective layer 17 and the first adhesive layer 12a.

[0103] [Exterior material manufacturing method] Next, there will be described an example of a method for manufacturing the exterior packaging material 10 shown in Fig. 1. Note that the method for manufacturing the exterior packaging material 10 is not limited to the following method.

[0104] The manufacturing method of the exterior material 10 of this embodiment is roughly composed of a step of providing corrosion prevention treatment layers 14a, 14b on the barrier layer 13, a step of bonding the base material layer 11 and the barrier layer 13 together using a first adhesive layer 12a, a step of further laminating a sealant layer 16 via a second adhesive layer 12b to produce a laminate, and a step of, if necessary, subjecting the obtained laminate to an aging treatment.

[0105] (Laminating process of corrosion prevention treatment layers 14a, 14b on barrier layer 13) This step is a step of forming the corrosion prevention treatment layers 14a, 14b on the barrier layer 13. As described above, examples of the method include subjecting the barrier layer 13 to a degreasing treatment, a hydrothermal conversion treatment, an anodizing treatment, or a chemical conversion treatment, or applying a coating agent having corrosion prevention properties.

[0106] Furthermore, when the corrosion prevention treatment layers 14a, 14b are multiple layers, for example, a coating liquid (coating agent) constituting the lower corrosion prevention treatment layer (barrier layer 13 side) may be applied to the barrier layer 13 and baked to form a first layer, and then a coating liquid (coating agent) constituting the upper corrosion prevention treatment layer may be applied to the first layer and baked to form a second layer.

[0107] The degreasing treatment may be performed by spraying or immersion. The hydrothermal conversion treatment and anodizing treatment may be performed by immersion. The chemical conversion treatment may be performed by an appropriate method such as immersion, spraying, or coating, depending on the type of chemical conversion treatment.

[0108] Regarding the coating method of the coating agent having corrosion prevention properties, various methods such as gravure coating, reverse coating, roll coating, bar coating, etc. can be used.

[0109] As described above, the various treatments may be performed on either one or both sides of the metal foil, but in the case of one-sided treatment, the treated side is preferably the side on which the sealant layer 16 is laminated. If required, the surface of the base layer 11 may also be subjected to the above treatments.

[0110] The amount of coating agent applied to form the first layer and the second layer is 0.005 to 0.200 g / m 2 is preferable, and 0.010 to 0.100 g / m 2 is more preferred.

[0111] Furthermore, when dry curing is required, it can be performed at a base material temperature in the range of 60 to 300° C. depending on the drying conditions of the corrosion prevention treatment layers 14a and 14b used.

[0112] (Step of bonding the base layer 11 and the barrier layer 13) This step is a step of bonding the barrier layer 13 provided with the corrosion prevention treatment layers 14a, 14b to the base material layer 11 via the first adhesive layer 12a. The bonding method may be dry lamination, non-solvent lamination, wet lamination, or the like, and the two are bonded together using the material constituting the first adhesive layer 12a described above. The first adhesive layer 12a has a dry coating amount of 1 to 10 g / m. 2 More preferably, the range is 2 to 7 g / m 2 It is set within the range.

[0113] (Laminating step of second adhesive layer 12b and sealant layer 16) This step is a step of bonding the sealant layer 16 via the second adhesive layer 12b to the second corrosion prevention treatment layer 14b side of the barrier layer 13. Examples of the bonding method include a wet process and dry lamination.

[0114] In the case of the wet process, the solution or dispersion of the adhesive constituting the second adhesive layer 12b is applied onto the second corrosion prevention treatment layer 14b, and the solvent is removed at a predetermined temperature to form a dry film, or the dry film is baked as necessary after the dry film is formed. Then, the sealant layer 16 is laminated to produce the exterior material 10. Examples of the coating method include the various coating methods exemplified above. The preferred dry coating amount of the second adhesive layer 12b is the same as that of the first adhesive layer 12a.

[0115] In this case, the sealant layer 16 can be produced, for example, by a melt extrusion molding machine using a resin composition for forming a sealant layer that contains the above-mentioned components of the sealant layer 16. In the melt extrusion molding machine, the processing speed can be set to 80 m / min or more from the viewpoint of productivity.

[0116] (Aging process) This step is a step of aging (curing) the laminate. By aging the laminate, it is possible to promote adhesion between the barrier layer 13, the second corrosion prevention treatment layer 14b, the second adhesive layer 12b, and the sealant layer 16. The aging treatment can be carried out at a temperature in the range of room temperature to 100°C. The aging time is, for example, 1 to 10 days.

[0117] In this manner, the exterior packaging material 10 of the present embodiment as shown in FIG. 1 can be manufactured.

[0118] Next, a description will be given of an example of a method for manufacturing the exterior material 20 shown in Fig. 2. Note that the method for manufacturing the exterior material 20 is not limited to the following method.

[0119] The manufacturing method of the exterior material 20 of this embodiment is generally configured to include a step of providing the corrosion prevention treatment layers 14a, 14b on the barrier layer 13, a step of bonding the base material layer 11 and the barrier layer 13 together using the first adhesive layer 12a, a step of further laminating the adhesive resin layer 15 and the sealant layer 16 to prepare a laminate, and a step of heat treating the obtained laminate, if necessary. Note that the steps up to the step of bonding the base material layer 11 and the barrier layer 13 can be performed in the same manner as the manufacturing method of the exterior material 10 described above.

[0120] (Laminating Step of Adhesive Resin Layer 15 and Sealant Layer 16) This step is a step of forming an adhesive resin layer 15 and a sealant layer 16 on the second corrosion prevention treatment layer 14b formed in the previous step. The method includes a method of sand laminating the adhesive resin layer 15 together with the sealant layer 16 using an extrusion laminator. Furthermore, lamination is also possible by a tandem lamination method in which the adhesive resin layer 15 and the sealant layer 16 are extruded, or a co-extrusion method. In forming the adhesive resin layer 15 and the sealant layer 16, for example, each component is blended so as to satisfy the above-mentioned configuration of the adhesive resin layer 15 and the sealant layer 16. The above-mentioned resin composition for forming the sealant layer is used to form the sealant layer 16.

[0121] This process produces a laminate in which the layers are stacked in the following order: base layer 11 / first adhesive layer 12a / first corrosion prevention treatment layer 14a / barrier layer 13 / second corrosion prevention treatment layer 14b / adhesive resin layer 15 / sealant layer 16, as shown in FIG. 2.

[0122] The adhesive resin layer 15 may be laminated by directly extruding the materials dry-blended to have the above-mentioned material composition using an extrusion laminator. Alternatively, the adhesive resin layer 15 may be laminated by extruding the granulated material, which has been melt-blended in advance using a melt kneading device such as a single-screw extruder, a twin-screw extruder, or a Brabender mixer, using an extrusion laminator.

[0123] The sealant layer 16 may be laminated by directly extruding the materials dry-blended to have the above-mentioned material composition as the constituents of the resin composition for forming the sealant layer using an extrusion laminator. Alternatively, the adhesive resin layer 15 and the sealant layer 16 may be laminated by a tandem lamination method in which the adhesive resin layer 15 and the sealant layer 16 are extruded using an extrusion laminator using a granulated product obtained by melt blending in advance using a melt kneading device such as a single screw extruder, a twin screw extruder, or a Brabender mixer, or by a co-extrusion method. Alternatively, a sealant monolayer may be formed in advance as a cast film using the resin composition for forming the sealant layer, and this film may be laminated together with an adhesive resin by a method of sand lamination. The forming speed (processing speed) of the adhesive resin layer 15 and the sealant layer 16 may be, for example, 80 m / min or more from the viewpoint of productivity.

[0124] (Heat treatment process) This step is a step of heat-treating the laminate. Heat-treating the laminate can improve adhesion between the barrier layer 13, the second corrosion prevention treatment layer 14b, the adhesive resin layer 15, and the sealant layer 16. As a method of heat treatment, it is preferable to treat at a temperature at least equal to or higher than the melting point of the adhesive resin layer 15.

[0125] In this manner, the exterior packaging material 20 of this embodiment as shown in FIG. 2 can be manufactured.

[0126] Although preferred embodiments of the exterior material for an all-solid-state battery according to the present disclosure have been described in detail above, the present disclosure is not limited to such specific embodiments, and various modifications and changes are possible within the scope of the gist of the present disclosure described in the claims.

[0127] [All-solid battery] FIG. 4 is a perspective view showing one embodiment of an all-solid-state battery produced using the above-mentioned exterior material. As shown in FIG. 4, the all-solid-state battery 50 is configured to include a battery element 52, two metal terminals (current extraction terminals) 53 for extracting current from the battery element 52 to the outside, and an exterior material 10 that hermetically encloses the battery element 52. The exterior material 10 is the exterior material 10 according to the above-mentioned embodiment, and is used as a container for accommodating the battery element 52. In the exterior material 10, the base layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, the exterior material 10 is configured to enclose the battery element 52 inside by folding one laminate film in two and heat-sealing the periphery, or by overlapping two laminate films and heat-sealing the periphery, so that the base layer 11 is on the outer side of the all-solid-state battery 50 and the sealant layer 16 is on the inner side of the all-solid-state battery 50. The metal terminal 53 is sandwiched and sealed by the exterior material 10 that forms a container with the sealant layer 16 on the inside. The metal terminal 53 may be sandwiched by the exterior material 10 via a tab sealant. In the all-solid-state battery 50, the exterior material 20 or the exterior material 30 may be used instead of the exterior material 10.

[0128] The battery element 52 is formed by interposing a sulfide-based solid electrolyte between a positive electrode and a negative electrode. The metal terminal 53 is a part of a current collector taken out of the exterior material 10, and is made of a metal foil such as copper foil or aluminum foil. In the all-solid-state battery 50 of this embodiment, when hydrogen sulfide is generated from the battery element 52, the layer containing the color developer of the exterior material 10 changes color, so that an abnormality in the all-solid-state battery 50 can be visually detected at an early stage. EXAMPLES

[0129] The present disclosure will be described more specifically below based on examples, but the present disclosure is not limited to the following examples.

[0130] [Materials used] The materials used in the examples and comparative examples are shown below. <Protective layer (thickness 3 μm)> A protective layer-forming composition was used, which was prepared by mixing a base material, Vylon UR1400 (manufactured by Toyobo Co., Ltd.), with a curing agent, Takenate A-50 (manufactured by Mitsui Chemicals Co., Ltd.).

[0131] <Base layer (thickness 15 μm)> A nylon (Ny) film (manufactured by Toyobo Co., Ltd.) was used.

[0132] <First adhesive layer (thickness 5 μm)> A polyurethane adhesive (manufactured by Toyo Ink Co., Ltd.) was used, which is a mixture of a polyester polyol-based base material and a tolylene diisocyanate adduct-based curing agent.

[0133] <First corrosion prevention treatment layer (base layer side) and second corrosion prevention treatment layer (sealant layer side)> (CL-1): A sodium polyphosphate-stabilized cerium oxide sol was used, the solid content of which was adjusted to 10% by mass using distilled water as a solvent. The sodium polyphosphate-stabilized cerium oxide sol was obtained by mixing 100 parts by mass of cerium oxide with 10 parts by mass of sodium salt of phosphoric acid. (CL-2): A composition consisting of 90% by mass of "polyallylamine (manufactured by Nitto Boseki Co., Ltd.)" adjusted to a solid content concentration of 5% by mass using distilled water as a solvent, and 10% by mass of "polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation)" was used.

[0134] <Barrier layer (thickness 40 μm)> Annealed and degreased soft aluminum foil (manufactured by Toyo Aluminum Co., Ltd., "Material 8079") was used.

[0135] <Adhesive resin layer (thickness 20 μm)> As the adhesive resin, a random polypropylene (PP)-based acid-modified polypropylene resin composition (manufactured by Mitsui Chemicals, Inc.) was used.

[0136] <Sealant layer (thickness 60 μm)> A polypropylene-polyethylene random copolymer (manufactured by Prime Polymer Co., Ltd., product name: F744NP) was used as the resin composition for forming the sealant layer.

[0137] <Developer> In the examples, the following color developers a to c were added to the protective layer, the first adhesive layer, the adhesive resin layer, or the sealant layer. The presence or absence of addition and the blending amount are shown in Table 1. The blending amount indicates the ratio (mass %) to the total amount (100 mass %) of each layer. The color developers were mixed with the materials constituting each layer. Developer a: Lead acetate (Pb(CH3COO)2) Developer b: Copper sulfate (CuSO4) Developer c: Silver sulfate (Ag2SO4)

[0138] <Hydrogen sulfide (H2S) adsorbent> In some examples and comparative examples, the following hydrogen sulfide adsorbing substances a to c were added to the first adhesive layer, adhesive resin layer, or sealant layer. Table 1 shows whether they were added and the amount of addition. The amount of addition indicates the ratio (mass%) of the total amount (100 mass%) of each layer. The hydrogen sulfide adsorbing substance was mixed with the material constituting each layer. When the color developer and / or the hydrogen sulfide adsorbing substance was added to the adhesive resin layer or the sealant layer, it was mixed in advance with a part of the resin constituting the adhesive resin layer or the sealant layer, and then the mixture was mixed with the remaining material constituting each layer. When the color developer and / or the hydrogen sulfide adsorbing substance was added to the first adhesive layer, it was mixed in advance with the base material constituting the first adhesive layer, and then the mixture was mixed with the curing agent. Hydrogen sulfide adsorbent a: Zinc oxide (ZnO, white pigment) Hydrogen sulfide adsorption material b: Dainichiseika Color & Chemicals Mfg. Co., Ltd., product name: Daimshoe PE-M 3000-Z (polyethylene masterbatch product) Hydrogen sulfide adsorption material c: Manufactured by Toagosei Co., Ltd., product name: Kesmon NS10C (general deodorant)

[0139] [Creating exterior materials] (Examples 1 to 4 and 7 to 17) First, a first and a second corrosion prevention treatment layer were provided on the barrier layer by the following procedure: (CL-1) was applied on both sides of the barrier layer in a dry coating amount of 70 mg / m 2 The layer was then coated by microgravure coating so that the thickness of the layer was 200 mm, and the layer was baked at 200° C. in a drying unit. Next, (CL-2) was applied onto the layer obtained in a dry coating amount of 20 mg / m 2 By applying the coating by microgravure coating so that the above-mentioned coating conditions were satisfied, a composite layer consisting of (CL-1) and (CL-2) was formed as the first and second corrosion prevention treatment layers. This composite layer exhibits corrosion prevention performance by combining the two types of materials, (CL-1) and (CL-2).

[0140] Next, the first corrosion prevention treatment layer side of the barrier layer provided with the first and second corrosion prevention treatment layers was attached to the base layer by dry lamination using a polyurethane adhesive (first adhesive layer). The lamination of the barrier layer and the base layer was performed by applying a polyurethane adhesive to the surface of the barrier layer facing the first corrosion prevention treatment layer so that the thickness after curing would be 5 μm, drying at 80°C for 1 minute, laminating it with the base layer, and aging it at 60°C for 72 hours.

[0141] Next, the laminate of the barrier layer and the base material layer was set on the unwinding section of an extrusion laminator, and the adhesive resin layer (thickness 20 μm) and the sealant layer (thickness 60 μm) were laminated in this order on the second corrosion prevention treatment layer by co-extrusion at 270°C and 100 m / min. Note that the adhesive resin layer and the sealant layer were prepared by previously preparing compounds of various materials using a twin-screw extruder, and then used in the above extrusion lamination after undergoing a water-cooling and pelletizing process.

[0142] The laminate thus obtained was subjected to a heat treatment so that the maximum temperature of the laminate reached was 190° C., thereby producing an exterior material (a laminate of substrate layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer / adhesive resin layer / sealant layer). In each example, the developer and / or hydrogen sulfide adsorbent was added to the layers shown in Table 1 in the amounts shown in Table 1.

[0143] (Examples 5 to 6) First, a protective layer-forming composition was applied on the substrate layer by reverse coating and dried to form a protective layer having a thickness of 3 μm. Next, a laminate of a barrier layer and a substrate layer with a protective layer was obtained in the same manner as in Example 1. An adhesive resin layer and a sealant layer were laminated on the second corrosion prevention treatment layer in the obtained laminate of the protective layer, substrate layer, and barrier layer in the same manner as in Example 1, and heat treatment was performed to prepare an exterior material (a laminate of protective layer / substrate layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer / adhesive resin layer / sealant layer). In each example, the developer was added to the layer shown in Table 1 in the amount shown in Table 1.

[0144] (Example 18) An exterior material (a laminate of substrate layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer / adhesive resin layer / sealant layer) was produced in the same manner as in Example 1, except that the barrier layer was made of annealed and degreased soft aluminum foil in which pinholes were previously provided at a density of 1 pinhole per 5 cm square.

[0145] Comparative Example 1 An exterior material (a laminate of substrate layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer / adhesive resin layer / sealant layer) was prepared in the same manner as in Example 1, except that no color developer or hydrogen sulfide adsorbing substance was added to any of the layers.

[0146] Comparative Example 2 An exterior material (a laminate of substrate layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer / adhesive resin layer / sealant layer) was prepared in the same manner as in Comparative Example 1, except that a hydrogen sulfide adsorbing substance was added to the sealant layer in the compounding amount shown in Table 1.

[0147] [Measurement of outer / inner laminate strength] The exterior material was cut into a size of 15 mm x 200 mm, and when measuring the outer layer laminate strength, the barrier layer was partially peeled off from the base material layer, and when measuring the inner layer laminate strength, the barrier layer was partially peeled off from the sealant layer to form a portion for chucking the sample, and a sample for measuring laminate strength was obtained. A T-peel test was performed on this sample using a tensile tester (manufactured by Shimadzu Corporation) at a tensile speed of 50 mm / min. The measurement was performed in a room temperature (25°C) environment. The results are shown in Table 1.

[0148] [Heat seal strength measurement] The exterior material was cut into a size of 120 mm x 60 mm, folded in half so that the sealant layer was on the inside, and the end opposite the folded part was heat-sealed over a width of 10 mm at 190°C / 0.5 MPa / 3 seconds, and stored at room temperature for 6 hours. Then, the center of the longitudinal direction of the heat-sealed part was cut into a width of 15 mm x 30 mm (see Figure 5) to prepare a sample for measuring heat seal strength. A T-peel test was performed on the heat-sealed part of this sample using a tensile tester (manufactured by Shimadzu Corporation) at a tensile speed of 50 mm / min. The measurement was performed in a room temperature (25°C) environment. The results are shown in Table 1.

[0149] [Evaluation of color development] The exterior material was cut into a size of 50 mm x 50 mm to prepare a sample for evaluating color development. This sample was subjected to one of the following tests (1) to (5). Then, the layer of the sample to which the color developer was added was visually checked for discoloration. When discoloration was confirmed, it was rated as "A," and when no discoloration was confirmed, it was rated as "B." The results are shown in Table 1. (1) When the developer was added to the layer on the inner side (sealant layer side) of the barrier layer (Examples 2 to 3, 7, and 16) The sample was placed in a 2L Tedlar bag and attached to the bag with the sealant layer facing the inside of the bag. At this time, the periphery of the sample was fixed with tape to prevent H2S from getting into the base layer side. In this state, the Tedlar bag was sealed. 2L of H2S gas with a concentration of 5 mass ppm was poured into the Tedlar bag and left at room temperature (25°C) for 72 hours. (2) When the developer was added to the layer on the outer side (substrate layer side) of the barrier layer (Examples 1, 5, 8 to 15, and 17) The sample was placed in a 2L Tedlar bag and attached to the bag so that the base layer side or the protective layer side faced the inside of the bag. At this time, the periphery of the sample was fixed with tape to prevent H2S from getting into the sealant layer side. In this state, the Tedlar bag was sealed. 2L of H2S gas with a concentration of 5 mass ppm was poured into this Tedlar bag and left at room temperature (25°C) for 72 hours. (3) When the developer was added both inside and outside the barrier layer (Examples 4 and 6) Both tests (1) and (2) above were performed and a rating was given for each. When discoloration was confirmed in both cases, it was rated as "A", and when discoloration was not confirmed in either or both cases, it was rated as "B". (4) When a barrier layer having pinholes was used (Example 18) In order to detect H2S penetrating through pinholes, the test described above in (1) was carried out. (5) When no developer was added (Comparative Examples 1-2) Both tests (1) and (2) above were performed and a rating was given for each. If one or both discolorations were observed, the test was rated as "A", and if neither discoloration was observed, the test was rated as "B".

[0150] [Evaluation of hydrogen sulfide (H2S) absorption] The exterior material was cut into a size of 50 mm x 50 mm to prepare a sample for evaluating H2S absorption. This sample was subjected to one of the following tests (1) to (3). The H2S concentration in the Tedlar bag was then measured, and a concentration of 5 ppm by mass or less was rated as "A," and a concentration of more than 5 ppm by mass was rated as "B." The results are shown in Table 1. (1) When an H2S adsorbent was added to the layer on the inner side (sealant layer side) of the barrier layer (Examples 7 to 8, 10 to 13, and 17, Comparative Example 2) The sample was placed in a 2L Tedlar bag and attached to the bag with the sealant layer facing the inside of the bag. At this time, the periphery of the sample was fixed with tape to prevent H2S from getting into the base layer side. In this state, the Tedlar bag was sealed. 2L of H2S gas with a concentration of 20 mass ppm was poured into the Tedlar bag and left at room temperature (25°C) for 144 hours. (2) When an H2S adsorbent was added to the layer outside the barrier layer (on the substrate layer side) (Example 9) The sample was placed in a 2L Tedlar bag and attached to the bag so that the base layer side or the protective layer side faced the inside of the bag. At this time, the periphery of the sample was fixed with tape to prevent H2S from getting into the sealant layer side. In this state, the Tedlar bag was sealed. 2L of H2S gas with a concentration of 20 mass ppm was poured into the Tedlar bag and left at room temperature (25°C) for 144 hours. (3) When no H2S adsorbent was added (Examples 1 to 6, 14 to 16, 18, Comparative Example 1) Both tests (1) and (2) above were performed, and the result with the lower H2S concentration was used for the judgment.

[0151] [Table 1] [Industrial Applicability]

[0152] According to the exterior material for an all-solid-state battery disclosed herein, when hydrogen sulfide is generated, the color of the layer containing the color developer in the exterior material changes, and therefore, abnormalities in the all-solid-state battery can be detected early by visual inspection. [Explanation of symbols]

[0153] Reference Signs List 10, 20, 30...exterior material for all-solid-state battery, 11...substrate layer, 12a...first adhesive layer, 12b...second adhesive layer, 13...barrier layer, 14a...first corrosion prevention treatment layer, 14b...second corrosion prevention treatment layer, 15...adhesive resin layer, 16...sealant layer, 17...protective layer, 50...all-solid-state battery, 52...battery element, 53...metal terminal.

Claims

1. An exterior material for an all-solid-state battery including a sulfide-based solid electrolyte, comprising at least a substrate layer, a barrier layer, and a sealant layer in this order, The laminate further includes at least one of a first adhesive layer disposed between the base layer and the barrier layer, a second adhesive layer disposed between the barrier layer and the sealant layer, and an adhesive resin layer disposed between the barrier layer and the sealant layer; at least one layer selected from the group consisting of the first adhesive layer, the second adhesive layer, the adhesive resin layer, and the sealant layer contains a color developer that changes color upon reaction with hydrogen sulfide; The all-solid-state battery exterior material, wherein the color developer contains at least one selected from the group consisting of CuSO 4 , Pb(CH 3 COO) 2 and Ag 2 SO 4 .

2. An exterior material for an all-solid-state battery including a sulfide-based solid electrolyte, comprising at least a substrate layer, a barrier layer, and a sealant layer in this order, the adhesive layer further comprises at least one of a first adhesive layer disposed between the base layer and the barrier layer, a second adhesive layer disposed between the barrier layer and the sealant layer, and an adhesive resin layer disposed between the barrier layer and the sealant layer, and a protective layer disposed on a surface of the base layer opposite to the barrier layer side, at least one layer selected from the group consisting of the protective layer, the first adhesive layer, the second adhesive layer, the adhesive resin layer, and the sealant layer contains a color developer that changes color upon reaction with hydrogen sulfide; The all-solid-state battery exterior material, wherein the color developer contains at least one selected from the group consisting of CuSO 4 , Pb(CH 3 COO) 2 and Ag 2 SO 4 .

3. 3. The exterior material for an all-solid-state battery according to claim 1, wherein a content of the color developer in the layer containing the color developer is 0.01% by mass or more and 30% by mass or less based on a total amount of the layer.

4. The all-solid-state battery exterior material according to any one of claims 1 to 3, wherein at least one of the layers constituting the exterior material contains a hydrogen sulfide adsorption material that does not fall under the category of the color developer.

5. 5. The all-solid-state battery exterior material according to claim 4, wherein, when the base material layer side of the all-solid-state battery exterior material is an outer side and the sealant layer side is an inner side, at least one layer of layers arranged on the inner side of the barrier layer contains the color developer, and at least one layer of the layer containing the color developer and the layer arranged on the barrier layer side thereof contains the hydrogen sulfide adsorption material.

6. The all-solid-state battery exterior material according to claim 4 or 5, wherein the hydrogen sulfide adsorption substance contains zinc oxide and / or zinc ions.

7. 7. The all-solid-state battery exterior material according to claim 4, wherein a total content of the developer and the hydrogen sulfide adsorption substance in the layer containing the developer is 0.01 mass % or more and 30 mass % or less based on a total amount of the layer.

8. The all-solid-state battery exterior material according to any one of claims 1 to 7, wherein a corrosion prevention treatment layer is provided on one or both surfaces of the barrier layer.

9. A battery element including a sulfide-based solid electrolyte; a current extracting terminal extending from the battery element; The all-solid-state battery exterior material according to any one of claims 1 to 8, which holds the current extraction terminal and houses the battery element; An all-solid-state battery equipped with

Citation Information

Patent Citations

  • Copper compound-containing functional material and manufacturing method of the same

    JP2003339836A

  • Nonaqueous electrolyte secondary battery and battery pack as well as manufacturing method of nonaqueous electrolyte secondary battery and battery pack

    JP2008004506A

  • All-solid battery

    JP2008103283A

  • All-solid battery

    JP2008103288A

  • Tarnishable ultrafine metal particle-containing composition and method for determining deodorization

    JP2009209200A